Weeds as Reservoirs of Plant Pathogens Affecting Economically Important Crops - Morgan Byron; Danielle D Treadwell; Peter J. Dittmar (EDIS, 2019)
Weeds are a major contributor to yield loss and reduction in yield quality in an agricultural setting, competing with the crop for resources like light, water, and nutrients. This competition along with the cost of weed management strategies like tillage and herbicides, are responsible for the economic impact of weeds, which can reach into the billions. In addition to the damage caused by direct competition, weeds can also harm crop plants by acting as reservoirs for destructive plant pathogens, the insect vectors that move these pathogens from plant to plant, or both. The objective of this publication is to summarize previously published weed-pathogen associations to help growers scout and monitor pathogens in weeds near production areas. https://edis.ifas.ufl.edu/hs1335